A river health assessment of selected South-Western Cape Rivers : index of habitat integrity, water quality and the influence of surrounding land use - Dawson, Emily Kathleen (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2003.